GIS Based Landslide Hazard Mapping Prediction in Ulu Klang, Malaysia - Muhammad Mukhlisin; Ilyias Idris; Al Sharif Salazar; Khairul Nizam; Mohd Raihan Taha (Institute for Research and Community Services (LPPM) ITB, 2010)
Since 1993, a number of landslides have been reported in Ulu Klang, Malaysia. These landslides caused fatalities and economic losses. Most of these landslides occurred in man-made slopes. Geographical Information System (GIS) is proposed to be used as the based machine for the production of landslide hazard map. This study highlights the area based landslide hazard assessment at Ulu Klang area using GIS application in order to help the engineer or the town planner to identify the most suitable development area besides predicting the potential landslide hazard area. Four main factors that influence of landslide occurrence were chosen include slope gradient aspect, geology, surface cover/land used and precipitation distribution. Landslide hazardous areas were analyzed and mapped using GIS application and produced a hazard map with five different indexes (i.e., very low, low, medium, high and very high hazard). The results of the analysis were verified using the landslide location data. The result showed that the model was very suitable in predicting landslide hazard and generating landslide hazard maps.